Seamount egg‐laying grounds of the deep‐water skate Bathyraja richardsoni. Issue 2 (28th June 2016) - Henry, L.‐A.; Stehmann, M. F. W.; De Clippele, L.; Findlay, H. S.; Golding, N.; Roberts, J.M.
Abstract : Highly localized concentrations of elasmobranch egg capsules of the deep‐water skate Bathyraja richardsoni were discovered during the first remotely operated vehicle (ROV) survey of the Hebrides Terrace Seamount in the Rockall Trough, north‐east Atlantic Ocean. Conductivity–temperature–depth profiling indicated that the eggs were bathed in a specific environmental niche of well‐oxygenated waters between 4·20 and 4·55° C, and salinity 34·95–35·06, on a coarse to fine‐grained sandy seabed on the seamount's eastern flank, whereas a second type of egg capsule (possibly belonging to the skate Dipturus sp.) was recorded exclusively amongst the reef‐building stony coral Solenosmilia variabilis . The depths of both egg‐laying habitats (1489–1580 m) provide a de facto refuge from fisheries mortality for younger life stages of these skates.